On the occassion of the sale of one million LP's of 'World Star Festival' issued for the benefit of the world's refugees. U Thant right, left Aga Khan United Nations High Commissioner for Refugees
On the occassion of the sale of one million LP's of 'World Star Festival' issued for the benefit of the world's refugees. U Thant right, left Aga Khan United Nations High Commissioner for Refugees.